Estimation of genetic parameters, character associations and path analysis for fruit yield and its components in Ber (Ziziphus muriatiana Lamarck) (Indian Journal of Arid Horticulture, 2025)
Arid region in India is spread over 38.70 million ha covers about 12 per cent of the total area of the country. The tracts of hot arid region are found in the states of Rajasthan (19.6 m ha) followed by Gujarat (6.2 m ha), Andhra Pradesh (2.2 m ha), Punjab (1.5 m ha), Haryana (1.3 m ha), Karnataka (0.8 m ha) and Maharashtra (0.1 m ha). Farming being a difficult task in the arid tropics, the agro-climate of such regions favours the cultivation of certain fruit crops. Indian jujube (Ziziphus mauritiana Lamk.) commonly known as Ber belonging to family Rhamnaceae, is indigenous to India and is one of the important fruit trees that can be successfully cultivated in the hot arid regions of India. The fruits of Indian jujube are rich in vitamin C, A and B complex. In Punjab it is cultivated on 2,894 ha having annual production 43,410 mt (Anon. 2006). Out of more than 90 cultivars only 11 are commonly cultivated commercially in different agro climatic regions of India (Morton 2005).
Keywords: important; Maharashtra